1989
DOI: 10.1002/poc.610020505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of carbon vs. oxygen regioselectivity in reactions of gas‐phase enolate ions

Abstract: A gas-phase experimental investigation of the competition between carbon and oxygen alkylation of a series of cyclic and acyclic enolate ions is described. Perfluoropropylene is shown to react in a characteristic way with oxyanions and carbanions to produce distinctive ionic products. The relative yields of these products formed in reactions with ambident enolate ions provides a measure of their intrinsic carbon vs. oxygen regioselectivity. The results for a series of enolates derived from aldehydes, ketones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
(5 reference statements)
2
24
1
Order By: Relevance
“…One explanation involves the energy difference between the keto and enol tautomers (∆H KE ) of the carbonyl compound. 11 A thermodynamic argument works in this case because the kinetically controlled ratios have been shown to be a reflection of the initial reaction step energetics (i.e. carbanion vs. oxy anion attack).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation involves the energy difference between the keto and enol tautomers (∆H KE ) of the carbonyl compound. 11 A thermodynamic argument works in this case because the kinetically controlled ratios have been shown to be a reflection of the initial reaction step energetics (i.e. carbanion vs. oxy anion attack).…”
Section: Resultsmentioning
confidence: 99%
“…Ambident species having two different reaction sites are well known in organic chemistry (Klopman, 1974). Enolate anions are such species that in reactions with pentafluoroanisole (Ingemann et al, 1982) and hexafluoropropene (Brickhouse & Squires, 1989) had been found to react at both the oxygen and carbon center. From the systematic study with hexafluoropropene it was suggested that reaction at the oxygen center would be favored if the difference in heats of formation of the keto and enol forms of the neutral carbonyl compounds would be <60 kJ/mol (Brickhouse & Squires, 1989).…”
Section: The Years Of Fourier Transform Ion Cyclotron Resonance mentioning
confidence: 99%
“…Enolate anions are such species that in reactions with pentafluoroanisole (Ingemann et al, 1982) and hexafluoropropene (Brickhouse & Squires, 1989) had been found to react at both the oxygen and carbon center. From the systematic study with hexafluoropropene it was suggested that reaction at the oxygen center would be favored if the difference in heats of formation of the keto and enol forms of the neutral carbonyl compounds would be <60 kJ/mol (Brickhouse & Squires, 1989). However, various enolate anions violated this criterion and some of them were observed in my group to react in an opposite way with regard to O/C site addition to the substrates hexafluorobenzene and hexafluoropropene (Freriks, de Koning, & Nibbering, 1991).…”
Section: The Years Of Fourier Transform Ion Cyclotron Resonance mentioning
confidence: 99%
“…Many factors affect the ambident reactivity, such as counter metal ions, structures, steric effects, and dielectric factor and hydrogen bonding of solvents, so on and so forth. Computational studies are also convenient to validate reaction mechanisms for ambident reactions .…”
Section: Introductionmentioning
confidence: 99%